2017
DOI: 10.3389/fmars.2017.00200
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Extracellular Enzymatic Activities in the Atlantic Ocean Follow Patterns Across Spatial and Depth Regimes

Abstract: Heterotrophic microbial communities use extracellular enzymes to initialize degradation of high molecular weight organic matter in the ocean. The potential of microbial communities to access organic matter, and the resultant rates of hydrolysis, affect the efficiency of the biological pump as well as the rate and location of organic carbon cycling in surface and deep waters. In order to investigate spatial-and depth-related patterns in microbial enzymatic capacities in the ocean, we measured hydrolysis rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 44 publications
13
30
0
Order By: Relevance
“…We found that the bacterial extracellular proteases show a clear depth trend, with mostly serine proteases in the surface water and metalloproteases in the deep water. These results agree with findings in previous studies (Arnosti et al, 2011 ; Steen et al, 2012 ; Tropeano et al, 2012 ; D'Ambrosio et al, 2014 ; Hoarfrost and Arnosti, 2017 ) and have important implications for microbial physiology and biogeochemical cycle in the ocean. Pantoja and Lee ( 1999 ) found that rates of peptide hydrolysis were greatly affected by the size and structure of the substrates; for example, peptides with more than two amino acids were hydrolyzed faster than dipeptides in natural seawater.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the bacterial extracellular proteases show a clear depth trend, with mostly serine proteases in the surface water and metalloproteases in the deep water. These results agree with findings in previous studies (Arnosti et al, 2011 ; Steen et al, 2012 ; Tropeano et al, 2012 ; D'Ambrosio et al, 2014 ; Hoarfrost and Arnosti, 2017 ) and have important implications for microbial physiology and biogeochemical cycle in the ocean. Pantoja and Lee ( 1999 ) found that rates of peptide hydrolysis were greatly affected by the size and structure of the substrates; for example, peptides with more than two amino acids were hydrolyzed faster than dipeptides in natural seawater.…”
Section: Discussionsupporting
confidence: 93%
“…These differences may be partially driven by biogeographical differences in microbial communities, with eddy or ring intrusions onto the continental shelf bringing with them a distinct microbial community (Nelson et al, 2014) with distinct hydrolytic capacities. The differences in functional capacities observed across sites and water masses are in keeping with functional biogeographical patterns in substrate hydrolysis previously identified across latitude, station, and depth (Arnosti et al, 2011(Arnosti et al, , 2012Hoarfrost and Arnosti, 2017), and between onshore and off-shore sites in the North Atlantic along similar scales of distance (D'Ambrosio et al, 2014). Differential longterm responses of the microbial communities in Stn.…”
Section: Discussionsupporting
confidence: 82%
“…The assemblage of enzymes that a microbial community can produce affects the nature and quantity of organic substrates that microbial communities can access, as well as the rates at which they are hydrolyzed (Arnosti, 2011). These functional patterns follow gradients across depth (Baltar et al, 2010b;Steen et al, 2012;Hoarfrost and Arnosti, 2017), latitude (Arnosti et al, 2011), hydrographic properties (Baltar and Arístegui, 2017;Hoarfrost and Arnosti, 2017;Balmonte et al, 2018), and between coastal and open ocean regions (D'Ambrosio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7). These latitudinal (Arnosti et al 2011) and depth-related trends (Hoarfrost et al 2017;Balmonte et al 2018), previously observed in bulk water, are also demonstrable in the particle-associated fraction. More importantly, differences in enzymatic activities in bulk water and on particles increase with increasing depth (Fig.…”
Section: Heterogeneous Latitudinal and Depth-related Trends Marine Msupporting
confidence: 71%